Adaptation and Validation into Spanish of the Jewish Religious Coping Scale “JCOPE” in an Orthodox Jewish Community - Simkin, Hugo (2024)
This study aims to assess the psychometric properties of the Spanish version of the Jewish Religious Coping Scale (JCOPE) within an Orthodox Jewish community in the Autonomous City of Buenos Aires, Argentina. 200 Orthodox Jews with ages between 18 and 66 years (M = 29.86; SD = 13.02) and of both sexes (men = 69%; women = 31%) participated in the study. A 2-factor model resulted in acceptable fit indices (NNFI = .94; CFI = .95; IFI = .95; SRMR = .65). Results indicated an acceptable internal consistency for both the positive (ω = .85) and negative Jewish religious coping (ω = .57). While its suggested its use, future research should continue to explore the psychometric properties of the JCOPE in Argentina.